2019
DOI: 10.1021/acs.jpcb.8b10859
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Properties Controlled by Substituents with Lone-Pair Electrons at the Ortho- or Para-Positions of Fluoroquinolone Antibiotics

Abstract: The ortho- or para-substituents of NH2 or N-alkyl-containing lone-pair electrons were found to change the energy levels and transition configurations of the highest occupied molecular orbital for some fluoroquinolone-based antibiotics (FQs) and can significantly influence the electronic structure, intermolecular hydrogen bonding, internal conversion, and fluorescence and intersystem crossing efficiencies of FQs in acetonitrile or aqueous solution after photoexcitation. These findings provide new insights that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…The electron-donating capacity of the N-group is a key factor affecting the excited states of FQs . It has been shown that the N-containing group on the C-5 and C-7 positions in the structures of FQ molecules elevated the energy level of HOMO, which narrows the HOMO–LUMO gap and favors the IC process, while a FQ without N-containing substituent group, flumequine, exhibited high ISC efficiency . Since there is no N-containing substituent group on the C-5 and C-7 positions in its structure, and the NH moiety in the side chain could only have a weak contribution to the HOMO, GRNX might undergo a strong ISC process when exposed to sunlight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron-donating capacity of the N-group is a key factor affecting the excited states of FQs . It has been shown that the N-containing group on the C-5 and C-7 positions in the structures of FQ molecules elevated the energy level of HOMO, which narrows the HOMO–LUMO gap and favors the IC process, while a FQ without N-containing substituent group, flumequine, exhibited high ISC efficiency . Since there is no N-containing substituent group on the C-5 and C-7 positions in its structure, and the NH moiety in the side chain could only have a weak contribution to the HOMO, GRNX might undergo a strong ISC process when exposed to sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…27 It has been shown that the N-containing group on the C-5 and C-7 positions in the structures of FQ molecules elevated the energy level of HOMO, which narrows the HOMO−LUMO gap and favors the IC process, while a FQ without N-containing substituent group, flumequine, exhibited high ISC efficiency. 28 Since there is no N-containing substituent group on the C-5 and C-7 positions in its structure, and the NH moiety in the side chain could only have a weak contribution to the HOMO, GRNX might undergo a strong ISC process when exposed to sunlight. In contrast, levofloxacin and trovafloxacin, which have an N-containing substituent group on the C-7 position of their structures, are expected to undergo a moderate IC process under light irradiation.…”
Section: Introductionmentioning
confidence: 99%